Effect of processing on viscosity and molecular weight of (1,3)(1,4)-ß-glucan in western australian oat cultivars - Mitra, S.; Lahnstein, J.; James, Tony; Fenton, Haelee; Burton, R.; Cato, L.; Solah, Vicky (A A C C International, 2017)
Six Australian milling oat cultivars grown over two growing seasons were characterized for differences in (1,3)(1,4)-ß-glucan (ß-glucan) viscosity, solubility, molecular weight (Mw), and the effect of processing. Oat cultivars grown in 2012 had significantly higher extracted ß-glucan viscosity from oat flour than the same oat cultivar grown in 2011 (P < 0.05, mean 137 and 165 cP, respectively). Noodle ß-glucan mean viscosity for 2012 (147 cP) was significantly higher than for 2011 (128 cP). ß-Glucan from 'Williams' and 'Mitika' oats had the highest viscosity (P < 0.05) in flour (5.92 and 5.25%, respectively) and noodles (1.64 and 1.47%, respectively) for both years, compared with the other oat cultivars. ß-Glucan (Mw) of Williams for 2012 and 'Kojonup' for both years were the least affected by processing, with an average drop of 33% compared with a maximum of 63% for other cultivars. Therefore, Williams showed superior ß-glucan properties to other oat cultivars studied, and can potentially provide improved health benefits. High and low ß-glucan Mw populations were found in the same elution peak after processing. Oat cultivars chosen for processing should be those with ß-glucans that are more resistant to processing, and that maintain their physiochemical properties and, therefore, bioactivity.